Role of prostaglandins in tumour necrosis factor induced weight loss. - Mahony, S. M. (Nature Publishing Group, 1989)
Administration of either tumour necrosis factor alpha (TNF-alpha) or 16,16-dimethylprostaglandin E2 (PGE2) to female NMRI mice caused a decrease in body weight accompanied by a reduction in both food and water intake and a decrease in carcass water content. A single injection of TNF-alpha caused an enhanced production of PGE2 by spleen cells from treated animals, that was significant within 1 h of treatment, and persisted until at least 6 h. These results suggest that the anorectic effect of TNF-alpha may be mediated by a prostaglandin intermediate. Indomethacin (10 mg kg-1) administered 2 h before TNF-alpha (7.5 x 10(7) U kg-1) caused a significant reduction in the extent of weight loss and inhibited PgE2 production. Administration of indomethacin 0.5-1.5 h before the TNF-alpha had no significant effect on loss of body weight, but still inhibited PgE2 production. Also PgE2 production was still enhanced in response to TNF-alpha administered chronically, despite the inability of prolonged TNF-alpha administration to produce continued loss of body weight. These results suggest that prostaglandins are not involved in the anorectic effect of TNF-alpha.